2014
DOI: 10.1179/1476830514y.0000000134
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation of dates in Alzheimer's disease APPsw/2576 transgenic mice on oxidative stress and antioxidant status

Abstract: Oxidative stress may play a key role in Alzheimer's disease (AD) neuropathology. Changes in the oxidative stress, antioxidants, and membrane-bound enzymes were investigated in the cerebral cortex and hippocampus of AD transgenic mice model after long-term dietary supplementation of date palm fruits from Oman. The 4-month-old mice with double Swedish APP mutation (APPsw/Tg2576) were purchased from Taconic Farm, NY, USA; mice were fed two different doses of dates (such as 4 and 2%) or control diet for 15 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 60 publications
2
29
0
1
Order By: Relevance
“…We recently reported that chronic dietary term supplementation of fruits could be beneficial for behavior and oxidative stress related changes in AD transgenic mice[59606162] which also support our present findings.…”
Section: Discussionsupporting
confidence: 92%
“…We recently reported that chronic dietary term supplementation of fruits could be beneficial for behavior and oxidative stress related changes in AD transgenic mice[59606162] which also support our present findings.…”
Section: Discussionsupporting
confidence: 92%
“…These mice also 419 display defects in the hippocampal long-term potentiation and cerebel-420 lar motor function (Huang et al, 2013;Gabriel et al, 1999). Cattanach among others (De Felice et al, 2014;Hayashi et al, 2012;Kaur et al, 462 2014;Subash et al, 2014a;Subash et al, 2014b;Valenti et al, 2014). …”
mentioning
confidence: 94%
“…Hartman et al [61] pointed out that the antioxidant polyphenolic substances of pomegranate juice reduced amyloid load and improved behavior in an AD mouse. Subash et al [62] suggested that dietary supplementation of dates and figs improved cognitive and behavioral deficit via maintaining oxidant-antioxidant balances in APPsw/Tg 2576 transgenic AD mice. Nakajima et al [63] suggested that nobiletin significantly reduced oxidative stress and improved the cognitive impairment in a 3XTg-AD mouse model.…”
Section: Natural Products and Alzheimer's Diseasementioning
confidence: 99%
“…Hanish Singh et al [67] reported that ethanolic extract of Alpinia galangal improved the antioxidant status and inhibited the acetylcholine esterase activity in AD mice. Our research group from Oman reported the beneficial effects of natural products including pomegranate and figs on AD transgenic mice models [62, 6877]. …”
Section: Natural Products and Alzheimer's Diseasementioning
confidence: 99%